PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA MANAJERIAL PADA BUMN PTPN V PEKANBARU (Studi kasus kebun tandun BUMN PTPN V Pekanbaru) - Hetty Mariana Tanjung; Yusralaini '; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the effect of budget participation, organizational commitment and motivation to managerial performance. The method used in this study BUMN PTPN V in Pekanbaru. The population in this study were all employees of PTPN V (Persero) is involved in the process of participation (propose or implement) the budget, which includes managers, heads of sections, and subordinates. The research sample is census data retrieval techniques, because the entire population sampled, namely the 65 samples. testing the quality of the data used is data validity and reliability testing. The classical assumption used is normality test, multicolinearity, and test heterokedastisitas. Model analysis used multiple linear regression was used to analyze the data to help SPSS.20.0 program. penilitian results show that budget participation significant effect on managerial performance, commitment significant effect on managerial performance and motivation have a significant effect on managerial performance.Keywords: Participation budget, organizational commitment, motivation, And managerial performance.